Cost-return structure of dairy farming on marginal and small farms in sub-mountainous region of Punjab - SINGH, NAVNEET (Indian Journal of Dairy Science, 2017)
The present study was undertaken in sub-mountainous region of Punjab state having higher concentration of small farmers. We examined the cost-return structure of dairy farming and factors affecting value productivity of the milk produced. District Ropar and Hoshiarpur were randomly selected from sub-mountainous belt of the state followed by selection of 100 farmers randomly from four blocks of the districts with equal representation of marginal and small farmers in the sample. Our study revealed that present value of animals and construction of cattle shed constituted the major part of investment made in dairy enterprise. Main component of feed and fodder for all the milch animals was concentrates followed by expenses on dry fodder and green fodder. Mostly family labour was engaged in performing dairy farming related activities on the sample farms. Â Total cost of undertaking dairy enterprise worked out to be Rs 250424 on marginal and Rs 256824 on small farms while the gross returns from sale of milk and dung were Rs 310669 on marginal and Rs 329872 on small farms. The net returns per farm were higher on small farms (Rs 73048) as compared to marginal farms (Rs 60245) due to higher milk production on small farms. The functional analysis brought out that judicious use of green fodder, dry fodder, concentrates and labour can significantly enhance the value returns from buffalo and cow milk.